Mechanisms of Sex Differences in TNFR2 Mediated Cardioprotection - Wang, Meijing (2008)
BACKGROUND: TNFR1/TNFR2 signaling may mediate different cellular and molecular responses (injury vs. protection) and the balance may be affected by sex hormones. Previous studies have shown that females have improved myocardial functional recovery, TNFR1 signaling resistance, and increased SOCS3 expression following acute I/R when compared to males. However, it is unknown whether the TNFR2 pathway protects the myocardium from I/R injury, and if so, whether sex differences exist in TNFR2-mediated cardioprotection. Therefore, we hypothesized that: 1) TNFR2 mediates myocardial protection from I/R through STAT3, SOCS3 and VEGF in both genders; and 2) TNFR2 elicits greater protective signaling in females compared to males. METHODS AND RESULTS: Isolated male and female mouse hearts from TNFR2 knockout (TNFR2 KO), TNFR1/2KO and wild type (WT: C57BL/6J or B6129SF2/J) (n=5-6/group) were subjected to 20 minutes ischemia followed by 60 minutes reperfusion. TNFR2 deficiency decreased post-ischemic myocardial recovery in both genders, but had a greater effect on females. The deleterious effects of TNFR2 ablation were associated with a decrease in mRNA and protein levels of SOCS3, STAT3, and VEGF, as well as an increase in myocardial IL-1beta production in female hearts. However, a significant increase in JNK activation and IL-1beta protein levels were noted in male TNFR2KO hearts following I/R. Additionally, TNFR1/2 KO decreased myocardial function in female hearts, but not males. This observation was associated with a decrease in mRNA levels of SOCS3, STAT3 and VEGF, and an increase in myocardial p38 MAPK activation in females. CONCLUSIONS: Sex differences in the mechanisms of TNFR2 mediated cardioprotection occur by increasing STAT3, SOCS3, VEGF in females and by decreasing JNK in males.